Rekonstruksi Strategi Operasi Di Tengah Disrupsi Digital Dan Transformasi Global - Rudolf Eleazar (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
The advancement of digital technology and globalization has encouraged organizations to adapt their operational strategies to remain competitive. This study aims to analyze the impact of digital transformation on operations strategy through case studies of UPS and Starbucks. A qualitative case study approach was employed using secondary data from company reports and academic literature. The findings reveal that UPS utilizes automation, RFID, and Artificial Intelligence (AI) to enhance operational efficiency, speed, and reliability. Meanwhile, Starbucks implements an omnichannel strategy to improve customer experience and convenience. The study highlights that successful digital transformation depends not only on technology but also on human resource readiness, organizational culture, and the ability to build agility and resilience. Therefore, modern operations strategies should integrate technology, people, and organizational resilience to address global business challenges